Using ARMA Models in Stochastic Enterprise Valuation - Jöckel, Karl-Heinz; Pflaumer, Peter (Technische Universität Dortmund, 2024)
This article presents a method for estimating the variance of the firm or enterprise value distribution by incorporating temporal dependencies in cash flows using ARMA models. The analysis highlights the importance of considering these dependencies, as neglecting them can lead to a significant increase in variance and subsequent erroneous decision-making. By utilizing ARMA models, decision-makers can obtain a more accurate assessment of the underlying risks and make informed investment decisions based on a comprehensive understanding of the firm's value distribution. The proposed method provides valuable insights for evaluating the uncertainty associated with future cash flows and enhances the accuracy of investment decision processes.
Keywords: firm valuation; risk management in business; investment decision-making; autocorrelation; time series analysis; 310; Unternehmensbewertung; ARMA-Modell; Zeitreihenanalyse; Autokorrelation; Investitionsentscheidung; Risikomanagement